A report on a case of prurigo nodularis that responded to homeopathy (Indo-American Journal of Life Sciences and Biotechnology, 2024)
A benign, long-lasting neurodermatitis is called Prurigo nodularis (PN). We don't know the precise reason. Even with therapy, the nodules in the majority of PN instances do not completely disappear. An overview of the case: Here, an 18-year-old woman with a history of a 1-year-old eczematous lesion is diagnosed with PN. Natrium muriaticum, a homoeopathic remedy, was recommended based on the whole of the patient's symptoms. Over the course of four months, the patient's signs and symptoms progressively improved steadily and went into remission. Over the next year, there was no recurrence. It is clear from this case study that homoeopathy may be used as a therapeutic alternative to treat PN patients.